2010
DOI: 10.1007/s10745-010-9334-2
|View full text |Cite
|
Sign up to set email alerts
|

Capturing Community Context of Human Response to Forest Disturbance by Insects: A Multi-Method Assessment

Abstract: The socioeconomic and environmental features of local places (community context) influence the relationship between humans and their physical environment. In times of environmental disturbance, this community context is expected to influence human perceptual and behavioral responses. Residents from nine Colorado communities experiencing a large outbreak of mountain pine beetles (Dendroctonus ponderosae) were surveyed in 2007. Multiple analytic methods including ordinary least squares regression and multilevel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 20 publications
1
24
0
Order By: Relevance
“…For this reason, the implementation of a management policy that integrates ecological, economic and social concerns must also be based on an understanding of the cultural meaning of landscape. This cultural meaning varies from locality to locality, underscoring the importance of taking the local context seriously (Qin and Flint, 2010). This is especially relevant considering that allowing or emulating natural disturbance is increasingly becoming a management model for protected areas under the paradigm of protecting ecological integrity and nonequilibrium processes (Dearden and Dempsey, 2004;Zimmerer, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, the implementation of a management policy that integrates ecological, economic and social concerns must also be based on an understanding of the cultural meaning of landscape. This cultural meaning varies from locality to locality, underscoring the importance of taking the local context seriously (Qin and Flint, 2010). This is especially relevant considering that allowing or emulating natural disturbance is increasingly becoming a management model for protected areas under the paradigm of protecting ecological integrity and nonequilibrium processes (Dearden and Dempsey, 2004;Zimmerer, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…It thus attempts to answer the call for research across different cultural, socio-economic as well as ecological local contexts (Huntington et al, 2006;Qin and Flint, 2010). More than looking at the same phenomenon in a different location, the case of the Bavarian Forest shows that the local cultural meaning of the forest landscape makes for a specific trajectory of conflict about the management of natural disturbance.…”
Section: Introductionmentioning
confidence: 99%
“…Comparative community analysis and community context studies are two interrelated streams of inquiry in community research. Community social scientists have employed a range of methods to capture community contextual effects, such as typology construction, multi-level modeling, social network analysis, qualitative comparative analysis, and typical statistical analyses involving context variables [22,26,45,111]. This study shows that while community contextual understanding provides an important backdrop for the comparison of community cases, longitudinal comparative community research can in turn enrich the depiction of varied community contexts.…”
Section: Discussionmentioning
confidence: 95%
“…In a similar vein, Qin and Flint [22] examined the community contextual nature of local responses to forest disturbance by mountain pine beetles in north-central Colorado. The results indicated that community biophysical and socioeconomic characteristics directly influenced local participation in community actions related to the beetle outbreak, while also adjusting the relationships of individual-level variables with beetle-related activeness.…”
Section: Community Perceptions and Activeness In Response To Forest Imentioning
confidence: 99%
See 1 more Smart Citation